A Strategy Game Using Adaptive Agents and Reinforcement Learning - Doukas, Nikolaos; Bardis, Nikolaos; Drigas, Athanasios (Technium Education and Humanities, 2022)
This paper presents the functional specifications of a training platform for use in the training of cadets and serving officers. The game aims to teach trainees that their decisions need to be based both on strategic goals as well as on constraints imposed by international law concerning rules of engagement, ethical codes of conduct or environmental issues. Existing techniques bearing similarities to the required solution are presented. The importance of the problem is hence demonstrated and the possibilities for enhancing the quality of the learning experience for both students and instructors are explored. The rules of a computer game suitable for the cadets training are presented. The game is shown to be sufficient for use in the teaching of strategy ethics. The study leads to high level specifications for the design of the proposed training game. The functional design of the proposed game is then explained and its rules are listed. The design of adaptive software agents that are capable of assuming the role of non-player characters is presented. Further research work necessary for the development of optimization algorithms necessary for the design is described.